The Impact of the Nigeria Economy on Family Speech Communication of Igarra Rural Community of Edo State, Nigeria - CHUKWU, Obinna Johnkennedy; EVBOTOKHAI, Daniel Edekin (Integration: Journal Of Social Sciences And Culture, 2025)
Purpose:Millions of families attempting to survive amidst numerous economic obstacles are at the core of the Nigerian economy. From unemployment and inflation, to changes in oil prices and currency devaluation; families contend with an unstable economic environment that frequently determines their financial security and well-being. This paper explores how families interact and how they manage their limited resources. It also deals with the financial setbacks the nation imposes on family life.Methodology:It also demonstrates the Nigerian families' inventiveness and fortitude in the face of hardship, as well as their capacity for innovation and the creation of chances for economic emancipation. Hence, this paper underscores the intrinsic link between the Nigerian economy and family interaction.Findings:We shall be looking at the subject matter, studying the situation at Igarra Akoko-Edo local government in Edo state. The economy is a crucial aspect of every society. The economy of a state is the substructure of the state, and it is on this base that every other aspect of the society is built. Hence, Karl Marx refers to the political, social and religious aspects of the society as the superstructural aspect of the society.Implication:The superstructure can affect the base. However, he is of the view that the influence of the base is predominant. As such it becomes very essential that we look at this economic aspect of the society and how it affects the family which is a very important variable of the society.